2021
DOI: 10.15587/1729-4061.2021.247963
|View full text |Cite
|
Sign up to set email alerts
|

Determining the pectinesterase enzyme activity when storing table grape varieties depending on the degree of ripening

Abstract: Grapes are rich in easily digestible carbohydrates, mineral compounds, vitamins, phenolic compounds. and other vital components. It is known that fresh grapes can be used from September to December. To prolong the terms of consumption of this valuable raw material, the most appropriate varieties and conditions for storing grapes have been determined. White, pink, and red grape varieties were taken as the object of research. The changes in the activity of the pectinesterase enzyme were determined depending on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…These variants, which are characterized by the course of most of the extraction processes under conditions of excess CO 2 and trace amounts of oxygen, are characterized by "moderate oxidation" of phenolic substances, which, however, are marked by enzyme preparations. The presence of cellulolytic preparations is apparently accompanied by accelerated oxidation and condensation of phenolic substances [23], as a result of which the level of phenolic substances in wine materials obtained with glucanex turned out to be minimal. The most promising is the preparation of mixed-type action -Vinozyme and PEC 1 (Table 1), in the presence of which the mass concentration of phenolic substances in the wine material exceeds the control by more than 50 %.…”
Section: Discussion Of Results Of the Technology For The Production O...mentioning
confidence: 99%
“…These variants, which are characterized by the course of most of the extraction processes under conditions of excess CO 2 and trace amounts of oxygen, are characterized by "moderate oxidation" of phenolic substances, which, however, are marked by enzyme preparations. The presence of cellulolytic preparations is apparently accompanied by accelerated oxidation and condensation of phenolic substances [23], as a result of which the level of phenolic substances in wine materials obtained with glucanex turned out to be minimal. The most promising is the preparation of mixed-type action -Vinozyme and PEC 1 (Table 1), in the presence of which the mass concentration of phenolic substances in the wine material exceeds the control by more than 50 %.…”
Section: Discussion Of Results Of the Technology For The Production O...mentioning
confidence: 99%
“…The content of methyl alcohol in wines prepared from white grape varieties was 0.22÷0.23 g/dm 3 , and in wines prepared from red grape varieties this figure was relatively higher -0.34÷0.37 g/dm 3 . This means that red grape varieties have higher pectin content than white varieties [30].…”
Section: Studying the Quality Indicators Of Tokaj Wine Materialsmentioning
confidence: 99%
“…As a result of research [13], it was found that table grape varieties are rich in nutrients necessary for the human body, mainly simple sugars, organic acids, phenolic compounds, minerals, and iodine. Before storing fully ripened grape varieties, it was established that the enzymes ascorbate oxidase, o-diphenol oxidase, peroxidase, and catalase in their composition are constantly active and change differently.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%